Pendampingan Program Peningkatan Kemampuan Baca Tulis Huruf Pegon di TPQ Bustanul ‘Arifin Desa Kencong. Kepung. Kediri - Muhammad Alimudin Anas; Miftakhul Arif (LP3M IAIFA Kediri, 2020)
To be able to learn the Yellow Book that uses Arabic, then a student must be able to write and read pegon letters to interpret or translate Arabic books into Javanese or Indonesian. From the findings on the ground it turns out that students of grade IV TPQ Bustanul 'Arifin still can not read the writing well. Related to that, it is necessary to assist the program to improve the ability to read the writing of pegon letters. The research approach used in this research is the PAR method or Participatory Action Research.